2005
DOI: 10.1007/s00276-005-0334-7
|View full text |Cite
|
Sign up to set email alerts
|

The innervation of patella: anatomical and clinical study

Abstract: As much interest has been focused on afferent innervation of knee than that of patella, there are few articles about patellar innervation. But in clinical practice anterior knee pain due to patellar disorders is a quite frequent problem. Our aim was to review the innervation pattern of patella and to give the topographic anatomy of the nerves. We dissected 30 knees of 15 formaldehyde-fixed cadavers. Two nerves from vastus medialis and lateralis were found to reach patellar edge. Apart from these, we were unabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 9 publications
0
28
1
1
Order By: Relevance
“…The location of the FST-induced discomfort/tightness (the anterior thigh) was in agreement with results shown by Lai et al 13,14 The FST-reproduced patellar pain in patients with a positive FST was mainly located at the superior rim of the patella (FIGURE 2). As the medial and lateral patellar nerves enter the patella from its medial-and lateral-superior border, 18 this location of nerve entrance was consistent with the location of the reproduced anterior knee pain during the FST.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The location of the FST-induced discomfort/tightness (the anterior thigh) was in agreement with results shown by Lai et al 13,14 The FST-reproduced patellar pain in patients with a positive FST was mainly located at the superior rim of the patella (FIGURE 2). As the medial and lateral patellar nerves enter the patella from its medial-and lateral-superior border, 18 this location of nerve entrance was consistent with the location of the reproduced anterior knee pain during the FST.…”
Section: Discussionmentioning
confidence: 73%
“…Maralcan et al 18 showed that the femoral nerve played an important role in patellofemoral pain symptoms by giving local anesthetic injections to the medial and lateral patellar nerves in 20 patients with anterior knee pain, which significantly reduced the pain intensity. The femoral slump test (FST) is a neurodynamic test that can be used to assess the femoral component of the nervous system.…”
Section: T T Resultsmentioning
confidence: 99%
“…Definitely, Maralcan et al [17] reported that the patella had two nerve supplies, to the superomedial quadrants and to the superolateral quadrants, coursing within the substance of the vastus medialis and lateralis. The discovery could provide an anatomical evidence for orthopaedic surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…I would interpret their anatomic study in the fixed cadavers as confirming our observations reported in 1994. These authors then went on to confirm that these nerves are patellar pain afferents, by performing a local anesthesia block in 32 knees of 20 patients with patellofemoral pain [28]. They observed a significant difference between the visual analogue scale (VAS) scores before and after local anesthetic injections (p<0.01).…”
Section: Other Clinical Studiesmentioning
confidence: 99%
“…A recent study, from Turkey, evaluated the innervation of the patella in 30 knees of 15 formaldehyde-fixed cadavers [28]. A nerve from the vastus medialis, which is the nerve described above [1], entering the patella "superomedially", and a nerve "from the vastus lateralis, entering the patella superolaterally" were identified.…”
Section: Other Clinical Studiesmentioning
confidence: 99%